The participation of foreign bidders in EU public procurement: Too much or too little? - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2025)
This policy brief examines EU public procurement data from the Tenders Electronic Daily (TED) to evaluate foreign bidders' participation and success in winning EU public contracts. Despite data coverage limitations, the available information shows an increase in foreign participation in both full and partial contracts, with most activity concentrated in a few countries. Countries like the United States, Japan, and Canada focus on securing full contracts, while nations such as Norway and Turkey often engage through partial contracts. Notably, since Brexit, UK bidders have faced a significant decline in market share, benefiting other countries. The main conclusion is that foreign participation via cross-border procurement (Mode 1) - the only one available in the TED database - is not very high. Although it increased over time, it remains relatively modest, mainly due to low participation rates, rather than discriminatory practices. Between 2016 and 2019, only about 7 percent of EU procurement authorities received foreign bids. This fact alone largely explains the low level of cross-border procurement taking place via Mode 1: put simply, there is no winning without trying. Another important conclusion is that a comprehensive assessment of the participation of foreign bidders in EU procurement would require two new key metrics in the TED data collection process to capture the more important yet missing modes of international procurement. Having reliable and comprehensive data is not just an academic pursuit but a necessity for shaping effective EU policy in the face of rising global protectionism in public procurement.
Keywords: 330; EU-Vergaberecht; Ausschreibung; Internationale Geschäftsbeziehungen; EU-Staaten